PERLINDUNGAN HUKUM TERHADAP MITRA USAHA DALAM KONTRAK ELEKTRONIK (E-CONTRACT) DENGAN GRAB MERCHANT - Aprilia, Claressa; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The legal protection cannot be separated from human rights based on legal provisions and other legal policies, hereby related to the context of electronic contracts that occur between business partners and business providers, namely Grab Merchant. With this statement, the author takes the main issue, whether legal protection is needed for business partners in electronic contracts (e-contracts) with Grab Merchant service providers. In this writing, a research approach method is used with a normative approach that is qualitative descriptive in which there are secondary data elements consisting of library materials and other literature. That hereby in an electronic contract (e-contract) the business partner is only asked to read and then sign the contract unilaterally if agreeing to the content of the contract without having the opportunity to change the contract or raise an objection because the contract is caused by a difference in the contract clause which can conclude the legal consequences for the business actor, in this case Grab Merchant.Keywords: Legal Protections, Business Pertners, E-Contract, Grab Merchant.